Contribution of IL-1RI Signaling to Protection against Cryptococcus neoformans 52D in a Mouse Model of Infection - Shourian, Mitra; Ralph, Ben; Angers, Isabelle; Sheppard, Donald C.; Qureshi, Salman T. (Frontiers in Immunology, 2018)
Interleukin-1 alpha (IL-1α) and IL-1 beta (IL-1β) are pro-inflammatory cytokines that are induced following Cryptococcus neoformans infection and activate the IL-1 Receptor type I (IL-1RI). To establish the role of IL-1RI signaling in protection against cryptococcal infection, we analyzed wild type (WT) and IL-1RI-deficient (IL-1RI-/-) mice on the BALB/c background. IL-1RI-/- mice had significantly reduced survival compared to WT mice after intratracheal challenge with C. neoformans 52D. Microbiological analysis showed a significant increase in the lung and brain fungal burden of IL-1RI-/- compared to WT mice beginning at week 1 and 4 post-infection, respectively. Histopathology showed that IL-1RI-/- mice exhibit greater airway epithelial mucus secretion and prominent eosinophilic crystals that were absent in WT mice. Susceptibility of IL-1RI-/- mice was associated with significant induction of a Th2-biased immune response characterized by pulmonary eosinophilia, M2 macrophage polarization, and recruitment of CD4+ IL-13+ T cells. Expression of pro-inflammatory (IL-1α, IL-1β, IL-6, TNFα, MCP-1), Th1-associated (IFNγ, IL-12) and Th17-associated (IL-17A) cytokines was significantly reduced in IL-1RI-/- lungs compared to WT. WT mice also had higher expression of KC/CXCL1 and sustained neutrophil recruitment to the lung; however, antibody-mediated depletion of these cells showed that they were dispensable for lung fungal clearance. In conclusion, our data indicate that IL-1RI signaling is required to activate a complex series of innate and adaptive immune responses that collectively enhance host defense and survival following C. neoformans 52D infection in BALB/c mice.